Use of Topical or Systemic Steroids in Children with Upper Respiratory Tract Infection. (May 2013) - Esposito, S.; Bianchini, S.; Baggi, E.; Castellazzi, L.; Fumagalli, M.; Principi, N.
Steroids have long been used to improve a number of clinical conditions because of their role in reducing inflammatory responses, but their use has always been limited because of their possible long-term side effects. The aim of this review is to establish whether steroids can have a positive effect on the outcome of some pediatric upper respiratory tract infections. We used PubMed to select all of the studies on topical or systemic steroids, and their therapeutic use in children with rhinosinusitis (RS), acute otitis media (AOM), otitis media with effusion (OME), acute pharyngitis (AP), or periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis (PFAPA), published over the last 15 years. Although a generally significant improvement in signs and symptoms has been observed with the use of intranasal steroids in children with RS, it is not clear which molecule should be recommended, how long treatment should be continued, or whether the benefits are limited to allergic children. No high-quality studies on the use of topical or systemic steroids in AOM have been carried out, and the results of studies of OME are controversial. The potential positive effects of steroids in children with AP are too slight to justify their use, and their possible adverse effects (particularly in the case of repeated administration) have not been clearly evaluated. Oral corticosteroids seem to be effective in resolving the symptoms of PFAPA, although they do not prevent future fever cycles. These findings show that further randomised and controlled studies are required in order to approach upper respiratory tract infections correctly and avoid the risks associated with frequent steroid use.